CRISIS MANAGEMENT: CASE STUDY OF NYIRAGONGO VOLCANO ERUPTION 2021 IN DEMOCRATIC REPUBLIC OF CONGO - ZEHRAOUI, SABIHA (Digital Repository of Theses, 2023)
On 22nd May 2021, Nyiragongo volcano situated eastern Democratic Republic of Congo (DRC), erupted at 19:00 local time. Mount Nyiragongo, lies in the volcano region of Virunga National Park, near the border with Rwanda, 12 miles (19 km) north of Goma. Nyiragongo is known for its devastating eruptions (Rafferty, 2021). Increased volcanic activity earlier this year suggested an eruption was possible, but the Goma Volcano Observatory’s functions were hampered by funding cuts (Salazar, 2021). Prior to the eruption, no public statement was made about a potential eruption of Nyiragongo volcano, the population was directly confronted to the disaster without any preparations. Driven by a general sense of fear and panic, people rushed away from lava flows in all directions, which created intense traffic jams. 32 people died as a direct result of the eruption (either burned by the lava or asphyxiated by fumes), including three children (UNICEF, 2021a). The Government Spokesperson, Mr. Patrick Muyaya declared that 9 persons were dead in traffic (Sengenya, 2021). 450,000 people were displaced and evacuated after the Nyiragongo volcano erupts. On 23rd May 2021, DRC Government activates contingency plan and set up a crisis cell, comprising local authorities, the UN and the RCRC (Red Cross and Red Crescent) Movement (IFRC, 2021). The volcanic eruption comes at a time of acute ancillary humanitarian need in North Kivu and Ituri. A State of Siege was declared by the Government to be in force in the two provinces since early May (2021). Some 44 per cent of the 5.04 million IDPs (Internally Displaced Persons) in DRC are currently located in North Kivu. 3.2 million people are already in dire need of food assistance in a province that has the highest protection incidences (5,856) in the country (OCHA, 2021). To understand the circumstances and events that have influenced volcanic crisis management and emergency planning, the current research explored various aspects that have shaped the crisis management of the Nyiragongo volcano eruption 2021 in the Democratic Republic of Congo (DRC). To do that, a survey was conducted on 5000 people from Goma city including Nyiragongo. Eleven aspects were addressed in this survey: 1) facts about the Nyiragongo volcano environment and activity; 2) preparedness and early warning system; 3) contingency planning (emergency planning); 4) security and political context; 5) socio-economic realities; 6) health situation and COVID-19; 7) shelter, water, sanitation, and hygiene; 8) communication; 9) access and accessibility; 10) community and national engagement; and 11) international support. Although there is emergency planning for eventual volcano eruption in DRC; this research revealed that existing realities in the country made it so difficult to adapt and implement it in the field. Armed conflicts, poverty, malnutrition, COVID-19; all these complex facts have contributed to the volcano crisis management 2021 in DRC and much more. Therefore, this paper will be an important tool in developing effective preparedness and response planning for potential volcano eruptions. It will suggest also, an evidence-based source in volcano crisis management for tomorrow’s workforce in DRC and worldwide.